2008
DOI: 10.1002/pssc.200778499
|View full text |Cite
|
Sign up to set email alerts
|

Atmospheric‐pressure MOVPE growth of In‐rich InAlN

Abstract: This paper reports the atmospheric-pressure MOVPE growth of In-rich InAlN. All InAlN films prepared here (Al content:0 0.43) do not show phase separation. The incorporation of Al in InAlN is decreased with increasing growth temperature. A decrease in Al content is also observed for films grown at a position farther from the up-stream end of the susceptor. The marked decrease in the Al content along the gas flow direction seems to be caused by the shortage of TMA supply at the downstream by the parasitic reacti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0
2

Year Published

2009
2009
2013
2013

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 7 publications
0
17
0
2
Order By: Relevance
“…So, Kim-Chaveau et al considered AlInN MOVPE with In content less than 20% at 800 1C [8] and observed saturation of In content at PZ300 mbar, which indicates probable correlated loss of Al and In in their system. Simultaneously, growth of AlInN alloys with In content more than 60% at 730 Torr and 600-700 1C was demonstrated in [9,10]. Here, In content rises under the conditions providing dominant Al-related gas-phase parasitic chemistry.…”
Section: Model Descriptionmentioning
confidence: 81%
See 1 more Smart Citation
“…So, Kim-Chaveau et al considered AlInN MOVPE with In content less than 20% at 800 1C [8] and observed saturation of In content at PZ300 mbar, which indicates probable correlated loss of Al and In in their system. Simultaneously, growth of AlInN alloys with In content more than 60% at 730 Torr and 600-700 1C was demonstrated in [9,10]. Here, In content rises under the conditions providing dominant Al-related gas-phase parasitic chemistry.…”
Section: Model Descriptionmentioning
confidence: 81%
“…It is emphasized there that the data are obtained under low-pressure conditions ( $ 50 Torr) corresponding to weak parasitic reactions between TMAl and ammonia. Enhancement of the parasitic chemistry at a higher pressure was demonstrated in [8][9][10]. The effect seems to be related to the fact that high ammonia flows normally used for InN and InGaN growth may initiate parasitic reactions as applied to AlN growth.…”
Section: Introductionmentioning
confidence: 88%
“…Recently, attracted by AlInN 0.7-6.2 eV wide band-gap energy coverage and the resulting potential applications, we have developed an AlN buffer technology to grow high-quality indium-rich AlInN by metalorganic chemical vapor deposition ͑MOCVD͒. Using this technology, we can grow Al 0.2 In 0.8 N with full width at half maximum ͑FWHM͒ in ͑0002͒ / 2 scan ͑ scan͒ being 595 arc sec ͑2276 arc sec͒, which is much better than the reported MOCVD AlInN films, 10,11 and even some better than MBE-grown AlInN reported by Chiba university. 12 These high-quality AlInN films facilitate the re-examinations of the viewpoints of Naik et al 9 and Grille et al 7 To our surprise, it is found that they are both incorrect.…”
mentioning
confidence: 96%
“…The followings are the details of our research on the MOVPE InAlN growth [24]. Figure 11 shows the growth temperature dependence of In composition in InAlN films grown with a different TMI/(TMI+TMA) molar ratio.…”
Section: Status Of Inaln Solar Cell Researchmentioning
confidence: 99%